2013
DOI: 10.1080/21641846.2013.843812
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in multiple sclerosis

Abstract: Background: Fatigue is the most commonly reported symptom in multiple sclerosis (MS). Purpose: This brief narrative review addresses the clinical features, pathophysiology, and management of MS fatigue, as well as the varied approaches to its definition and measurement. Methods: A literature search was conducted through Medline of studies published since 1984, with a focus on findings reported since 2008. Results: Studies of MS fatigue have primarily relied on the definition of fatigue as a subjective sense of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 102 publications
0
14
0
1
Order By: Relevance
“…For example, trials of modafinil for fatigue management have shown mixed results with some trials failing to show a statistically significant effect on fatigue, and despite successful drug trials, no treatment is in routine clinical use. 4,10 While more studies are needed, these data present very promising signals for RS-tDCS as a non-pharmacological treatment for MS fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, trials of modafinil for fatigue management have shown mixed results with some trials failing to show a statistically significant effect on fatigue, and despite successful drug trials, no treatment is in routine clinical use. 4,10 While more studies are needed, these data present very promising signals for RS-tDCS as a non-pharmacological treatment for MS fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…7 Multiple factors are thought to contribute to fatigue 8,9 with no specific biomarker or etiology yet confirmed. 10 …”
Section: Introductionmentioning
confidence: 99%
“…MS is associated with a high (>70%) rate of cognitive impairment. Those with MS also suffer from other symptoms including mood, fatigue, sensory and motor problems that may respond to tDCS as well .…”
Section: Introductionmentioning
confidence: 99%
“…1 Fatigue is one of the most common and debilitating symptoms of MS; affecting up to 86% of people with MS, with two-thirds considering it to be one of their three worst symptoms. [2][3][4][5][6][7] In the UK it has been reported that the prevalence of MS is increasing with an estimated 126 669 people living with MS in the UK in 2010 (203.4 per 100 000 population) and 6003 new cases diagnosed that year (9.64 per 100 000/year). 8 Fatigue often occurs on a daily basis 2 and its invisible and unpredictable nature makes it a particularly frustrating symptom to cope with.…”
Section: Introductionmentioning
confidence: 99%